Ultrathin films of Pt on TiO2(110): Growth and chemisorption-induced surfactant effects - Steinrück, Hans-Peter; Pesty, François; Zhang, Lei; Madey, Theodore E. (Physical Review B, 1995)
The growth of ultrathin platinum films on a rutile TiO2(110) surface has been studied using low-energy ion scattering and x-ray photoelectron spectroscopy. In the temperature range between 160 and 420 K, Pt grows in three-dimensional islands on the TiO2 surface with the size of the islands increasing with increasing surface temperature and without indication of an interface reaction. Evaporation of Pt in the presence of CO leads to a significantly higher degree of wetting. This behavior is attributed to a chemisorption-induced surfactant effect. © 1995 The American Physical Society.